Answer:
x=-9
Step-by-step explanation:
first you make the coefficients equal to each other by doing a common factor which in this case is 5. Then you have to do the variable for each time the common number is repeated which is 5^x * 5^x= 5^(x+3)*5^(x+3)*5^(x+3) This would make it equal to 5^2x=5^(3x+9). Since the non exponents are common factors you can get rid of them and solve for the exponent by doing 2x=3x+9. You solve that equation to get x=-9.
Answer:
Either A or C, I'm not quite sure tho
Step-by-step explanation:
The line is on the negative side of the graph
(a) y = 2x + 3
(b) (1,5), (3,3); y = 3x + 3 5 = m1 + b, 3 = m3 + b
(c) coincident i believe, because it is not independent or inconsistent
(d) 2x + 3 = 3x + 3
(-2x)(-3) (-2x)(- 3)
0 = -2x
x = 0
hope this helps
Answer:
x=11(12y-15)
Step-by-step explanation:
4x(3y-2)=7x+11
12xy-8x=7x+11
12xy-8x-7x=11
12xy-15x=11
x(12y-15)=11
x(12y-15)/(12y-15)=11/(12y-15)
x=11/(12y-15)